KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA MELALUI MODEL PEMBELAJARAN CREATIVE PROBLEM SOLVING - Fitri, Wiva Rahmadona; Aprison, Wedra; Isnaniah, Isnaniah (Math Educa Journal, 2020)
This study discusses the problem in class X SMA Negeri 1 Bukittinggi about the learning model that is applied has not made students actively support. Students have difficulty solving real problems and problem-solving One alternative that can be used is to apply the Creative Problem Solving (CPS) learning model. The problem formulation is the problem solving the problem of students who follow the CPS learning model better about students who take conventional learning in class X IPA of SMA Negeri 1 Bukittinggi? The purpose of the study is the learning of problem-solving students who take the Creative Problem Solving (CPS) learning model better than students who take conventional learning in class X IPA of SMA Negeri 1 Bukittinggi in the 2019/2020 Academic Year. This type of research is a pre-experimental research design with The Static Group Comparison Design. The population is class X science students of SMA Negeri 1 Bukittinggi. While the sample is students of class X IPA-7 as an experimental class and class X IPA-6 as a control class. The instrument used was a test of the ability to solve mathematical problems consisting of essay tests. The data analysis technique uses t test which is supported by Minitab software. The results of t arithmetic = 2.54 and t-table = 1.67 because t-count> t table means that H0 is rejected at the real level α = 0.05, and by using Minitab obtained P-value = 0.007 which means P-value < α with a significant level α = 0.05 H_0 is rejected and H_1 is accepted. The Model of Problem Solving Creative Learning (CPS) is more about solving mathematical problems of students who use Creative Problem Solving (CPS) learning better than those who study in class X IPA of SMA Negeri 1 Bukittinggi 2019/2020 Academic Year.